Implementasi Pendidikan Karakter Islami dalam Program Keluarga Harapan (PKH) untuk Masyarakat Pedesaan : Studi Kasus di Desa Dawuhan - Nur Hidayatingsih; Ainur Rofiq Sofa (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The Family Hope Program (PKH) is a social assistance program aimed at improving the quality of life of underprivileged families through access to education, healthcare, and economic welfare. This article explores the implementation of Islamic character education within PKH, focusing on rural communities in Dawuhan Village. The study aims to analyze how Islamic values such as honesty, responsibility, hard work, and solidarity are applied in the daily lives of beneficiary families (KPM). The research employs a qualitative approach with data collection techniques including interviews, observations, and documentation. The findings reveal that Islamic character education in PKH serves as an effective tool to empower underprivileged families, not only by building individual morality but also by enhancing social cohesion and economic welfare. However, challenges such as low community participation, limited infrastructure, and cultural differences remain significant barriers. Recommendations from this study include enhancing the capacity of PKH facilitators, integrating Islamic values into educational modules, and fostering collaboration with religious institutions and local governments to ensure program sustainability. Islamic character education in PKH is expected to become a strategic solution for fostering sustainable social and economic transformation in rural communities